Impact of International Migration on Labor Supply in Nepal - Phadera, Lokendra (World Bank, Washington, DC, 2019)
This paper analyzes the differential impact of migration on labor supply of the left-behind household members in Nepal, where international migration for employment, predominantly a male phenomenon, increased substantially between 2001 and 2011. Using the Nepal Living Standard Survey data, the paper extends the analysis by incorporating the impacts on the extensive and intensive margins. The study also answer the question: if they are not wage-employed, in what activities are the remaining household members engaging instead? The paper finds that, in response to out-migration of some family members, women realign their priorities and reallocate their time from market employment to self-employment and home production, possibly filling in the roles vacated by the migrants. In contrast, the income effect dominates the impact of migration on the left-behind men; that is, men value their leisure more because of the remittances from abroad and decrease their overall supply of labor. Additionally, the research finds significant heterogeneity in the supply of labor by age, skill, and household head status among the left-behind women, pointing toward intrahousehold bargaining.